A brief history of mastoidectomy - Bento, Ricardo Ferreira; Fonseca, Anna Carolina de Oliveira (International Archives of Otorhinolaryngology, 2013)
Aim: To describe to the new generation of otologists the origins of mastoidectomy as well as the difficulties our predecessors encountered and the solutions they devised to improve otologic surgery.Method: Retrospective literature review-based study.Results: Before the mid-19th century, mastoidectomy was performed only sporadically and in most cases as a desperate attempt to save the lives of people suffering from complications of infectious otitis. The drainage of acute abscesses became a common procedure at the beginning of the 20th century, within the pre-antibiotic era. The first documented surgical incision to drain an infected ear was described by the French physician Ambroise Paré in the 16th century. The credit for performing the first mastoidectomy for the removal of purulent secretions went to Jean-Louis Petit. Mastoidectomies were normally performed to treat infections. However, mastoidectomies were also carried out for other purposes, particularly for the treatment of deafness and tinnitus, during various periods. Sir Charles Ballance credited Johannes Riolanus with recommending mastoidectomy for the treatment of tinnitus. William Wilde began the era of modern mastoidectomy with his introduction of the eponymous retroauricular incision.Conclusion: Mastoidectomy has evolved significantly throughout its history. Improvements in mastoidectomy have relied on the introduction of more elaborate surgical procedures, especially the advances in surgical equipment during the last century. Mastoidectomy continues to be a life-saving surgical procedure.
Keywords: Mastoid; History; Otolaryngology